Overweight Impairs Postural Control of Female Night Workers - Fernanda Veruska Narciso; Ana R. Dâmaso; Jose A. Barela; Adriana N. S. Carvalho; Francieli Ruiz; Sandra Souza de Queiroz; Vanessa Silva Lemos; Andre Gustavo P. de-Andrade; Sergio Tufik; Marco Túlio De-Mello (Sleep Science, 2023)
Objectives To verify the relationships between sleep duration (Total Sleep Time – TST) and postural control of female night workers before and after shift. As well as, to verify if there is an influence of the body mass index (BMI) on the postural control of these female workers before and after shift.